2013
DOI: 10.1001/jamaoto.2013.3554
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Laser- and Diathermy-Assisted Posterior Cordotomy for Bilateral Vocal Cord Abductor Paralysis

Abstract: clinicaltrials.gov Identifier: ISRCTN08093874.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…1 However, they also evaluated their patients with Dyspnea Severity Scale, and the rate of dyspnoea improvement was reported significantly lower in laser-assisted cordotomy which was attributed to the low thermal damage of lasers. 15 High decannulation rates are also reported in many previous studies. [16][17][18] Pulmonary function tests allow the physician to assess and dis- The results of this study support that both laser and diathermyassisted posterior chordotomy significantly improve pulmonary function outcomes and also correlate with other previous reports.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…1 However, they also evaluated their patients with Dyspnea Severity Scale, and the rate of dyspnoea improvement was reported significantly lower in laser-assisted cordotomy which was attributed to the low thermal damage of lasers. 15 High decannulation rates are also reported in many previous studies. [16][17][18] Pulmonary function tests allow the physician to assess and dis- The results of this study support that both laser and diathermyassisted posterior chordotomy significantly improve pulmonary function outcomes and also correlate with other previous reports.…”
Section: Discussionmentioning
confidence: 59%
“…Decannulation rate was 100% at the postoperative sixth month despite one postoperative tracheotomy in group 1 and two in group 2. Similarly, Mohammed et al reported 100% decannulation rates in their laser and diathermy‐assisted posterior chordotomy patients However, they also evaluated their patients with Dyspnea Severity Scale, and the rate of dyspnoea improvement was reported significantly lower in laser‐assisted cordotomy which was attributed to the low thermal damage of lasers . High decannulation rates are also reported in many previous studies …”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Respetar la integridad de los aritenoides y de la comisura posterior así como de las estructuras supraglóticas disminuye la tasa de posibles complicaciones [21,22]. Otros dispositivos diferentes al láser CO 2 se han descrito para la realización de esta técni-ca [23,24]. Sin embargo, todas presentan un índice similar de éxito por lo que el uso del láser carbónico resulta en nuestro caso de elección debido a la amplia experiencia que se dispone en su uso en cirugía oncológica.…”
Section: Resultsunclassified